Critical Evolution of Damage Toward System‐Size Failure in Crystalline Rock. Issue 2 (21st February 2018) - Renard, François; Weiss, Jérôme; Mathiesen, Joachim; Ben‐Zion, Yehuda; Kandula, Neelima; Cordonnier, Benoît
Abstract: Rock failure under shear loading conditions controls earthquake and faulting phenomena. We study the dynamics of microscale damage precursory to shear faulting in a quartz‐monzonite rock representative of crystalline rocks of the continental crust. Using a triaxial rig that is transparent to X‐rays, we image the mechanical evolution of centimeter‐size core samples by in situ synchrotron microtomography with a resolution of 6.5 μm. Time‐lapse three‐dimensional images of the samples inside the rig provide a unique data set of microstructural evolution toward faulting. Above a yield point there is a gradual weakening during which microfractures nucleate and grow until this damage span the whole sample. This leads to shear faults oriented about 30° to the main compressive stress in agreement with Anderson's theory and macroscopic failure. The microfractures can be extracted from the three‐dimensional images, and their dynamics and morphology (i.e., number, volume, orientation, shape, and largest cluster) are quantified as a function of increasing stress toward failure. The experimental data show for the first time that the total volume of microfractures, the rate of damage growth, and the size of the largest microfracture all increase and diverge when approaching faulting. The average flatness of the microfractures (i.e., the ratio between the second and third eigenvalues of their covariance matrix) shows a significant decrease near failure. The precursors to faulting developing in the future faulting zone are controlled by the evolving microfracture population. Their divergent dynamics toward failure is reminiscent of a dynamical critical transition. Key Points: The damage precursory to failure in a quartz‐monzonite rock is imaged at micrometer resolution A power law increase of damage rate and largest microfracture characterizes the road to faulting; failure stress is a critical point Variations in the shape parameters of microfractures are quantified and provide a new characterization of precursors to failure